Project MARIE: presentation and stage of development - Correia-da-Silva, J. J. (2014)
Project MARIE - Mediterranean Building Rethinking for Energy Efficiency Improvement is an international strategic project from the European Union in the scope of the MED Program. The project aims to promote building energy efficiency in the Mediterranean region and overcome the mains barriers to large scale improvement trough the development of a common strategy adaptable to each country/region specifications, in the framework of European Union building energy efficiency policies. This article presents a description of the Project MARIE, its stage of development, and also the results achieved in the first third of the project.